Pendampingan Pendidikan Dasar bagi Masyarakat Daerah Terpencil di Desa Bajeman Kabupaten Bangkalan - Taufiqur Rahman; Farid Ardyansyah; Ribka Bunga Satya Banjarnahor; Hairul Umur; Mohammad Syarifatul Mustofa; Misbahul Munir (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Education in remote areas faces complex challenges that affect the quality and equity of learning outcomes. This study aims to analyze various factors that hinder the educational process in Bajeman Village and to offer solutions based on Community Service Program (KKN) activities. The research employs a mixed-methods approach, collecting data through field observations, in-depth interviews, and questionnaires distributed to teachers, students, and community members. The findings indicate that the main challenges include a lack of qualified educators, inadequate infrastructure, low parental involvement, and limited internet access. Through KKN activities, the implemented solutions include digital literacy training for teachers, student learning assistance, and strengthening community participation in education. The objective of this study is to analyze various factors that hinder education in Bajeman Village and to propose solutions through the Community Service Program (KKN) in order to improve the quality of education and serve as a model for community service initiatives in other remote areas.